Parva universi e o direito de existir: o desenvolvimento sustentável na impenhorabilidade do pequeno imóvel rural por dívidas contraídas pela família camponesa - Leal , Miron Biazus (2019)
This scientific work seeks, through an in - depth study of the precepts attributed by the Brazilian legal system, to define and delimit the area of performance of the immobility of the small rural property worked by the peasant family entity for the sole purpose of subsistence. of legal, doctrinal and jurisprudential dogmas, the conceptualization and valuation of terms of interest, such as "small rural property", "peasant", "agrarian reform", besides the focus on sustainability, the debts that are covered by the institute of article 5, item XXVI, of the Federal Constitution of 1988, under the subsistence bias. As a result, the legal and jurisprudential distortion of the interpretation of peasants and of the institute of impenhorabilidad was identified, which led the Brazilian Courts, apart from the instruments of sustainability, to carry out partial or total expropriation of small rural properties in the face of debts contracted by the peasants. The scientific methods to elaborate the present work were: deductive, qualitative and bibliographical. As for the sources of research, contemporary and classical bibliographical references, jurisprudential understandings, articles and scientific journals, and other journals and magazines were used, founding a theoretical, doctrinal and pragmatic framework. As a result, we identified the judicial and doctrinal interpretations of peasants, allied to the sustainability institute, in the sense of the position used by the jurisprudence as to the impenorability of the small property in cases of partial or total expropriation of the small rural properties in the face of the debts contracted by the peasants.